On Performance and Accuracy of Lattice Boltzmann Approaches for Single Phase Flow in Porous Media: A Toy Became an Accepted Tool How to Maintain Its Features Despite More and More Complex (Physical) Models and Changing Trends in High Performance Computing!? - Zeiser, Thomas; Götz, Jan; Stürmer, Markus (Notes on Numerical Fluid Mechanics and Multidisciplinary Design, Computational Science and High Performance Computing III, 2008)
Delivering high performance on contemporary high performance computing architectures becomes more and more challenging owing to changing trends in computer hardware but also due to the incorporation of more complex physical models. Results from low level benchmarks and flow simulations using lattice Boltzmann approaches are reported for advanced HPC systems (NEC SX-8 vector parallel computer), commodity HPC clusters (based on Intel Woodcrest CPUs and Infiniband interconnect) and special purpose hardware (IBM Cell processor). © 2008 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-04-20:Pub.2008.tech.IMMD.lsinfs._onper